Endometrial safety of low-dose vaginal estrogens in menopausal women: a systematic evidence review. Issue 7 (July 2019) - Constantine, Ginger D.; Graham, Shelli; Lapane, Kate; Ohleth, Kathleen; Bernick, Brian; Liu, James; Mirkin, Sebastian
Abstract: Objective: The aim of the study was to systematically review studies that evaluated endometrial hyperplasia or cancer incidence with unopposed vaginal estrogens. Methods: PubMed and EMBASE were searched from inception to August 2017 for relevant articles and abstracts. Bibliographies of review articles and abstracts of major women's health medical meetings were examined. Eligible studies (independently reviewed by 4 authors) had to report menopausal vaginal estrogen use and endometrial histology, or incidence of endometrial hyperplasia or cancer. Results: Of 5, 593 abstracts from the literature search and 47 articles from other sources, 36 articles and 2 abstracts were eligible, describing 20 randomized controlled studies, 8 interventional studies, and 10 observational studies. Collectively, the studies did not support an increased risk of endometrial hyperplasia or cancer with low-dose vaginal estrogens. Rates of endometrial cancer and hyperplasia were 0.03% and 0.4%, respectively, from 20 randomized controlled trials (2, 983 women) of vaginal estrogens. Overall, reports of endometrial hyperplasia were observed with various doses and durations and appeared sporadic (except 1.25 mg conjugated equine estrogens), consistent with endometrial hyperplasia rates in the general population. A Denmark registry study was an exception and may be of limited applicability to the United States. The Women's Health Initiative Observational Study showed no association (1.3 cases/1, 000 women-years with vaginal estrogens versus 1.0/1, 000 women-years for nonuse). Conclusion: This systematic review supports the use of low-dose vaginal estrogens for treating vulvar and vaginal atrophy in menopausal women without a concomitant progestogen. This review does not support increased endometrial hyperplasia or cancer risk with low-dose, unopposed vaginal estrogens; however, longer-term, real-world data are needed. Abstract : Supplemental Digital Content is available in the text